COVID-19: A Source of Stress and Depression Among University Students and Poor Academic Performance - Jiang, Zuopeng; Jia, Xuhong; Tao, Ran; Dördüncü, Hazar (Frontiers in Public Health, 2022)
Current research examines how COVID19 has impacted the daily life of students, specifically personal and academic aspects. The authors investigated the role of academic and family stress caused by COVID19 on students' depression levels and the subsequent impact on their academic performance based on Lazarus' cognitive appraisal theory of stress. The non-probability convenience sampling technique has been used to collect data from undergraduate and postgraduate students using a modified questionnaire with a five-point Likert scale. This study used structural equation modeling to examine the link between stress, depression, and academic performance during COVID19. It was confirmed that educational and family stress significantly leads to depression among students, negatively affecting their academic performance and learning outcomes. This research provides valuable information to parents, educators, and other stakeholders concerned about their children's education and performance.